OIL GEOCHEMISTRY OF THE PUTUMAYO BASIM - J.C. RAMON (CT&F Ciencia, Tecnología & Futuro)
Biomarker fingerprinting of 20 crude oils from Putumayo Basin, Colombia, shows a vertical segregation of oil families. The Lower Cretaceous reservoirs (Caballos and "U" Villeta sands) contain oils that come from a mixture of marine and terrestrial organic matter, deposited in a marginal, "oxic" marine setting. The Upper Cretaceous ("T" and "N" sands) and Tertiary reservoirs contain oils with marine algal input deposited in a reducing, carbonate-rich environment. Lithology, environmental conditions and organic matter type of source rocks as predicted from oil biomarker differences correspond to organic composition of two Cretaceous source rocks. Vertical heterogeneity in the oils, even those from single wells, suggests the presence of two isolated petroleum systems. Hydrocarbons from Lower Cretaceous source rocks charged Lower Cretaceous reservoirs whereas oils from Upper Cretaceous source rocks charged Upper Cretaceous and Tertiary reservoirs. Oil migration from mature source rocks into multiple reservoirs has been stratigraphically updip along the "regional" sandstone units and vertical migration through faults has been limited. Biomarker maturity parameters indicate that all oils were generated from early thermal maturity oil window.